CORRELATION BETWEEN HEMOGLOBIN LEVEL AND LOW BIRTH WEIGHT AMONG PREGNANT WOMEN IN MANOKWARI, WEST PAPUA - Tjitradinata, Cynthia; Setiawan, I Edward Kurnia; Santoso, Ferry; Susianto, Indra Adi; Maya, Tiovani; Sutanto, Eviana Budiartanti; Sebong, Perigrinus Hermin (Jurnal Pranata Biomedika, 2026)
Introduction: Birth weight and its related maternal factors have significantly affected health throughout an individual’s life, particularly in western Indonesia. This study aims to reveal the effect of maternal anemia on low birth weight among newborns in General Hospital.Methods: A formative study was conducted from October to December 2023 in Manokwari, West Papua Province, Indonesia. We used secondary data from the birth cohort register 2022, including maternal socio-demographic information, health-related factors, antenatal visit details, and neonatal birth outcomes.Results: Pregnant women who give birth have an average gestational age of 28.80 (±1.08). The average hemoglobin level among pregnant women is 10.25 (±2.12), and the average newborn birth weight is 2932.9 (±447.1). Maternal age, educational status, employment status, infant gender, gestational age, and comorbidities do not correlate with birth weight. In contrast, hemoglobin levels with birth weight have a significant relationship between maternal hemoglobin levels and newborn birth weight.Conclusion: The study revealed that mothers with low hemoglobin levels are significantly associated with low birth weight among newborns at Manokwari Regional Hospital, West Papua. Future studies should be adjusted to explain pregnant women's iron levels and nutrition intake.